2020
DOI: 10.1242/bio.057042
|View full text |Cite
|
Sign up to set email alerts
|

The basal release of endothelium-derived catecholamines regulates the contractions of Chelonoidis carbonaria aorta caused by electrical-field stimulation

Abstract: The contractions of Chelonoidis carbonaria aortic rings induced by electrical field stimulation (EFS) are not inhibited by blockade of the voltage-gated sodium channels by tetrodotoxin but almost abolished by the α1/α2-adrenoceptor antagonist phentolamine. The objective of this study was to identify the mediator(s) responsible for the EFS-induced contractions of Chelonoidis carbonaria aortic rings. Each ring was suspended between two wire hooks and mounted in isolated 10 ml organ chambers filled with oxygenate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…In both tissues, the contractions induced by dopamine were blocked when the rings were preincubated with the dopamine D 2 -like antagonist, haloperidol ( 24 ). Similar results were observed in tortoise aortic rings, where preincubation with either haloperidol or quetiapine caused significant rightward shifts in the concentration-dependent contractions induced by dopamine ( 21 ).…”
Section: Endothelial-derived Dopaminesupporting
confidence: 73%
See 1 more Smart Citation
“…In both tissues, the contractions induced by dopamine were blocked when the rings were preincubated with the dopamine D 2 -like antagonist, haloperidol ( 24 ). Similar results were observed in tortoise aortic rings, where preincubation with either haloperidol or quetiapine caused significant rightward shifts in the concentration-dependent contractions induced by dopamine ( 21 ).…”
Section: Endothelial-derived Dopaminesupporting
confidence: 73%
“…Similar results were obtained with aortic rings of the venomous snakes Bothrops jararaca and rattlesnake ( 15 ) and in the aortic rings of the tortoise Chelonoidis carbonaria ( 18 ), where immunohistochemical detection of the neuromarker S100 protein ( 19 ) was negative in all aortic tunicae investigated, indicating the absence of nerve terminals in these vascular tissues ( 15 ). Another important piece of evidence for the existence of endothelial-derived catecholamines was the identification of the basal release of dopamine, noradrenaline, and adrenaline from tortoise isolated aortas detected by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) and the significant reduction observed on the release when the endothelial cells were removed by mechanical procedure ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In pre-contracted human umbilical vessels ( 4 ) and in Chelonoidis carbonarius aortic rings ( 5 ), the relaxations induced by 6-ND were similar to those induced by the dopamine D 2 -like receptor antagonist haloperidol, since they were not affected by pre-incubation with L-NAME but strongly reduced in endothelium-denuded rings. Dopamine is released by cultured endothelial cells ( 23 ), human umbilical cord arteries and vein ( 24 ), and Chelonoidis carbonaria aortic rings ( 25 ). Indeed, immunohistochemistry for tyrosine hydroxylase of both Crotalus durissus terrificus and Bothrops jararaca aortae revealed that this enzyme is present in endothelial cells ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that 6-ND inhibited EFS-induced contractions reinforced the novel concept of endothelium-derived catecholamines as main modulators of vascular reactivity ( 4 , 5 , 33 ). EFS causes contractions in vessels that are devoid of nerve terminals, such as human umbilical cord vessels ( 24 ), Chelonoidis carbonaria aortic rings ( 25 , 27 ), and Panterophis guttatus aortic rings ( 6 ). Since the contractions were strongly reduced by removal of the endothelium, it should be considered that endothelial cells in the vessel are excitable.…”
Section: Discussionmentioning
confidence: 99%